8-Electrode data collection system for electrical capacitance tomography - Rerkratn, Apinai; Lertpakdee, Thanakorn; Chitsakul, Kitiphol; Sangworasil, Manas; Petchmaneelumka, Wandee (My University, 2006)
8-electrode data collection system for electrical capacitance tomography is presented. The system mainly consists of a signal generator, 8×2 multiplexer, detector, amplifier, band-pass filter, rms-to-dc converter, A/D converter circuit and control computer. Experimental results with a circular sensor show that the proposed system is able to collect data with satisfy sensitivities, linearity, resolution and also being insensitive to noise. Reconstructed images from collected data are shown. © 2006 ICASE.
Keywords: Capacitance measurement; Data collection system; ECT; Process tomography